Trends and characteristics of naloxone therapy reported to US poison centers. (9th August 2018) - Rege, Saumitra V.; Ngo, Duc Anh; Ait‐Daoud, Nassima; Sharma, Sana; Verplancken, Evan; Holstege, Christopher P.
Abstract: Background and aims: In the United States, access to naloxone has been expanded as a measure to address growing opioid overdose mortality. The study aimed to describe the national trends in naloxone use as reported to the US poison centers (PCs). Methods: The National Poison Data System (NPDS) was queried for cases reporting naloxone therapy from 1 January 2001 to 31 December 2016. Demographic and clinical characteristics were assessed descriptively. Trends in naloxone reports were evaluated by using generalized linear mixed models that were adjusted for age, gender and random effects of the geographical census region. Cumulative incidence rates (CIR) of naloxone reports at the state‐ and national‐level were calculated. Results: There were 304 249 cases reporting naloxone therapy during the study period. The frequency of naloxone reports increased from 9498 in 2000 to 26 826 in 2016. The proportion of cases where naloxone was used prior to PC recommendation increased from 59.8% in 2000 to 81.5% in 2016. The mean number of NPDS naloxone reports per 100 000 human exposures increased from 9.6 [95% confidence interval (CI) = 6.4–14.2] to 31.7 (95% CI = 21.4–46.9, P < 0.001). Among the cases, 52.4% were female and the most frequent age group was 20–39 years (39.1%). The principal reason for a toxic exposure resulting in a naloxone report was suspected suicide (55.0%). Life‐threatening symptoms were seen in one‐fifth of the cases, with 53.9% cases being admitted to critical care units. Opioids (59.7% cases), were the most commonly reported exposure agents, with hydrocodone being most frequently reported. The national CIR of naloxone reports to the US PCs was 6.3 cases per 100 000 population, with West Virginia demonstrating the highest incidence. Conclusions: Analysis of calls to the United States poison centers indicates an increasing trend of naloxone use from 2000 to 2016.